Pediatric Oncology Providers' Attitudes and Practice Patterns Regarding Fertility Preservation in Adolescent Male Cancer Patients. Issue 2 (March 2016) - Fuchs, Amanda; Kashanian, James A.; Clayman, Marla L.; Gosiengfiao, Yasmin; Lockart, Barbara; Woodruff, Teresa K.; Brannigan, Robert E.
Abstract : Background: The aim of this study was to evaluate pediatric oncology providers' attitudes toward fertility preservation (FP), their use of educational materials, their approach to FP discussion, and their FP knowledge specifically pertaining to adolescent males. Methods: A 40-item online survey was distributed to physicians, advanced practice nurses (APN), and nurses within pediatric oncology. Results: About 78.7% of physicians, 81.4% of APN, and 51.9% of nurses reported high levels of comfort in discussing FP options with adolescent males ( P <0.05). Fifty-one percent of physicians and 54.2% of APN reported using educational materials, compared with 38.9% of nurses ( P <0.05). Regarding knowledge of FP technologies, 48.7% of physicians, 52.5% of APN, and 81.1% of nurses reported being unfamiliar with intracytoplasmic sperm injection ( P <0.05). An overwhelming majority (92.9%) of respondents reported having no formal training in discussing FP. Finally, 84.8% of respondents believed formal training on this issue would be useful to them. Conclusions: This study illustrates an unmet need in the education of pediatric oncology providers, as knowledge gaps and discomfort are common themes reported by health care professionals within the context of adolescent male FP care. In addition, this study reveals a high level of receptiveness to FP training by these same providers.